(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article explores the activities of libraries in Uzbekistan during World War II, focusing on changes in their material and technical base, the reduction of book collections, and the mobilization of library staff to the front. It also analyzes how libraries promoted patriotic and ideological literature and contributed to strengthening the spiritual unity and will of society through mass and educational events.